Assessing the feasibility of harm reduction services for MSM: the late night breakfast buffet study - Kellogg Timothy A; Raymond H Fisher; Rose Valerie J; McFarland Willi (BMC, 2006)
Abstract Background Despite the leveling off in new HIV infections among men who have sex with men (MSM) in San Francisco, new evidence suggests that many recent HIV infections are linked with the use of Methamphetamine (MA). Among anonymous HIV testers in San Francisco, HIV incidence among MA users was 6.3% compared to 2.1% among non-MA users. Of particular concern for prevention programs are frequent users and HIV positive men who use MA. These MSM pose a particular challenge to HIV prevention efforts due to the need to reach them during very late night hours. Methods The purpose of the Late Night Breakfast Buffet (LNBB) was to determine the feasibility and uptake of harm reduction services by a late night population of MSM. The "buffet" of services included: needle exchange, harm reduction information, oral HIV testing, and urine based sexually transmitted infection (STI) testing accompanied by counseling and consent procedures. The study had two components: harm reduction outreach and a behavioral survey. For 4 months during 2004, we provided van-based harm reduction services in three neighborhoods in San Francisco from 1 - 5 a.m. for anyone out late at night. We also administered a behavioral risk and service utilization survey among MSM. Results We exchanged 2000 needles in 233 needle exchange visits, distributed 4500 condoms/lubricants and provided 21 HIV tests and 12 STI tests. Fifty-five MSM enrolled in the study component. The study population of MSM was characterized by low levels of income and education whose ages ranged from 18 - 55. Seventy-eight percent used MA in the last 3 months; almost 25% used MA every day in the same time frame. Of the 65% who ever injected, 97% injected MA and 13% injected it several times a day. MA and alcohol were strong influences in the majority of unprotected sexual encounters among both HIV negative and HIV positive MSM. Conclusion We reached a disenfranchised population of MA-using MSM who are at risk for acquiring or transmitting HIV infection through multiple high risk behaviors, and we established the feasibility and acceptability of late night harm reduction for MSM and MSM who inject drugs.